Pharmacovigilance study of famciclovir in the Food and Drug administration adverse event reporting system database - Runan Fang; Yang Zhou; Lu Han; Wenjing Chen; Ning Guan; Jianhong Li (Scientific Reports)
Abstract Famciclovir, mainly used to treat herpes zoster, is rapidly transforms into penciclovir when administered orally. Our study evaluated adverse events (AEs) associated with famciclovir by mining data from the publicly available Food and Drug Administration Adverse Event Reporting System (FAERS) database, providing a reference for clinical safety. Disproportionality analysis (including reported odds ratio and proportional reporting ratio) and Bayesian methods (including Bayesian Confidence Propagation Neural Network and Gamma-Poisson Shrinkage) were used to quantify the AE signals associated with famciclovir. A total of 17,652,186 case reports were obtained from the FAERS database, and 432 famiclovir-related AEs were identified. Nausea, headache, altered mental status, vomiting, and dizziness were found to be the most common Aes, corresponding to those reported in the Food and Drug Administration (FDA) drug labelling and clinical trials. Our study found some potential AEs of famciclovir that were not mentioned in the FDA drug labelling, such as toxic encephalopathy, encephalopathy, ataxia, dysarthria, dementia, cerebral infarction, tremor, purpura, skin ulcers, acute pancreatitis, rhabdomyolysis, muscle twitching, increased blood urea, lowered blood pressure, hepatitis, disease recurrence, drug interactions, and pancytopenia. Our study identified potential famciclovir AE signals, providing insights for physicians to reduce possible side effects and promote the safe implementation of the drug in clinical settings.